2004
DOI: 10.1017/s1740925x04000304
|View full text |Cite
|
Sign up to set email alerts
|

Oligodendrocytes assist in the maintenance of sodium channel clusters independent of the myelin sheath

Abstract: To ensure rapid and efficient impulse conduction, myelinated axons establish and maintain specific protein domains. For instance, sodium (Na+) channels accumulate in the node of Ranvier; potassium (K+) channels aggregate in the juxtaparanode and neurexin/caspr/paranodin clusters in the paranode. Our understanding of the mechanisms that control the initial clustering of these proteins is limited and less is known about domain maintenance. Correlative data indicate that myelin formation and/or mature myelin-form… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
60
0

Year Published

2005
2005
2016
2016

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 62 publications
(63 citation statements)
references
References 44 publications
(45 reference statements)
2
60
0
Order By: Relevance
“…These data indicate that oligodendrocytes actively regulate the complement and localization of Nav channels expressed in CNS axons. Consistent with this idea, Dupree et al (2004) reported, using the cuprizone model of CNS demyelination and remyelination, that demyelinated CNS axons have clusters of Nav1.2 channels, and that nodes in the remyelinated corpus callosum eventually have only Nav1.6 channels. Thus, clustering of Nav channels during CNS remyelination might recapitulate developmental myelination.…”
Section: Nav Channel Subtypes At Nodes Of Ranvier During Remyelinatiomentioning
confidence: 66%
See 3 more Smart Citations
“…These data indicate that oligodendrocytes actively regulate the complement and localization of Nav channels expressed in CNS axons. Consistent with this idea, Dupree et al (2004) reported, using the cuprizone model of CNS demyelination and remyelination, that demyelinated CNS axons have clusters of Nav1.2 channels, and that nodes in the remyelinated corpus callosum eventually have only Nav1.6 channels. Thus, clustering of Nav channels during CNS remyelination might recapitulate developmental myelination.…”
Section: Nav Channel Subtypes At Nodes Of Ranvier During Remyelinatiomentioning
confidence: 66%
“…The phenomenon of reversion from Nav1.6 as the main Nav channel subunit in axons to Nav1.2 as the main channel subunit is not restricted to mutant mouse models, but also occurs after demyelination in multiple sclerosis (Craner et al, 2004b). Interestingly, Dupree et al (2004) detected Nav1.2 clusters during remyelination in the CNS (in the corpus callosum), similar to those seen during developmental myelination.…”
Section: Role Of Myelination In Nav Channel Subtype Switchingmentioning
confidence: 76%
See 2 more Smart Citations
“…Deletion of oligodendrocyte-specific expressed genes can have a dramatic effect on axon maintenance and localization of neuronal proteins without strongly affecting myelin structure (Griffiths et al, 1998;Lappe-Siefke et al, 2003;GarciaFresco et al, 2006). Oligodendrocytes also are important for nodal sodium channel clustering, and this seems to be independent of myelin (Dupree et al, 2005). Combined deletion of FGF receptor-2 and CNP in oligodendrocytes led to massive hyperactivity, possibly as a result of an indirect effect of oligo- Ϫ/Ϫ (B) mice, which were morphologically indistinguishable.…”
Section: Although Fa2hmentioning
confidence: 99%